Protection of Indigenous Peoples’ Land Rights in Agrarian Reform Policy: A Normative and Implementational Legal Study - Salwa Aulia Novitasari; Arief Fahmi Lubis; Dila Padila Nurhasanah (West Science Law and Human Rights, 2026)
This study examines the protection of Indigenous Peoples’ land rights within the framework of agrarian reform policy through a normative and implementational legal analysis. The research aims to analyze the extent to which existing legal frameworks recognize and protect Indigenous land rights, identify inconsistencies within regulatory structures, and evaluate the effectiveness of their implementation in practice. Employing a normative juridical approach, this study analyzes constitutional provisions, statutory regulations, and relevant legal doctrines, complemented by a qualitative assessment of implementation challenges. The findings reveal that although Indigenous land rights are formally recognized in the legal system, such recognition remains conditional and fragmented across sectoral regulations. Overlapping authorities between land, forestry, and other resource-related laws create legal uncertainty and hinder the effective protection of customary land. Furthermore, the implementation of agrarian reform policies often fails to accommodate the collective nature of Indigenous land tenure, resulting in the marginalization of Indigenous communities. Bureaucratic complexities, limited institutional coordination, and weak enforcement mechanisms further exacerbate these challenges, leading to persistent land conflicts and dispossession. This study highlights a significant gap between normative legal guarantees and practical realities. It emphasizes the need for a more integrative and responsive legal framework that harmonizes regulations, strengthens the recognition of customary land rights, and ensures meaningful participation of Indigenous Peoples in agrarian reform processes. By bridging normative analysis with implementation perspectives, this research contributes to the development of more equitable and inclusive land governance systems that uphold Indigenous rights and promote social justice.